Digital Forensic Analysis Of Michat Application On Android As Digital Proof In Handling Online Prostitution Cases - Mahendra, Kadek Dwi Oka; Ari Mogi, I Komang (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana); Vol 9 No 3 (2021): JELIKU Volume 9 No 3, Februari 2021, 2021)
Smartphone technology and the Internet are very popular lately, especially with various features, one of which is instant messaging. But behind it all, instant messaging like MiChat is very vulnerable to becoming a crime, one of which is Online Prostitution. To follow up on Online Prostitution activities, it is necessary to carry out mobile forensics to find evidence which is then given to be given to the authorities. This study uses the MiChat application as an online prostitution media, and uses the National Institute of Justice (NIJ) method which has five basic stages is, preparation, collection, examination, analysis, and reporting. This research uses MOBILedit Forensic Express, and SysTools SQLite Viewer.